The Economic Impact of the 42nd ASEAN Summit in Labuan Bajo on The Accommodation Sector (Case Study: Residence House Rented) - Berybe, Gregorius; Palupi , Santi; Rudiyanto , Roseven; Jopang , Gaspar (International Ecsis Association, 2024)
The Meeting, Incentive, Convention, and Exposition (MICE) industry is very important for Indonesia because it directly provides benefits for entrepreneurs in the tourism sector and contributes to improving the quality of the community's economy. The MICE industry also provides benefits to the people of Labuan Bajo as a host. The 42nd ASEAN Summit 2023 is proof of readiness to organize international-scale events. Based on the objective conditions of the field, the occupancy rate reaches 100%, and many parties are constrained by accommodation. This study aims to see the direct economic impact obtained by the community on the accommodation sector. This research uses the qualitative descriptive analysis method where data is collected through observation, interviews, and literature from related party sources. The participants involved came from community groups in 4 sub-districts in West Manggarai Regency. The collected data is analyzed, reduced, verified, and drawn conclusions. The results showed that there were more than 50 houses rented with duration from 7 to 16 days. The rental price of residents' houses is from the range of 12 to 30 (million units). The price difference is caused by: The size of the house, number of rooms, facilities, mileage, and negotiation skills. Total income from renting houses reached IDR 1,206,000,000. It is concluded that there is an economic turnover (positive) from renting houses due to supply (accommodation) being lower than demand (visitors). This is a new finding for Labuan Bajo as a destination where residents' homes as an alternative when the accommodation is full.